Serological screening test for infectious mononucleosis using papain-treated sheep erythrocytes. Issue 4 (July 1966) - Robinson, L.; Smith, H.
Abstract : A screening test for infectious mononucleosis is described, based on the fact that antibodies against sheep red cells remaining after absorption of the serum by papain-treated sheep red cells appear to be specific for the disease. The test appears to be more useful in diagnosis than classical absorption techniques and has the advantage of being specific while maintaining a high degree of sensitivity.